The prevalence rate of sexual violence worldwide: a trend analysis - Nasrin Borumandnia; Naghmeh Khadembashi; Mohammad Tabatabaei; Hamid Alavi Majd (BMC, 2020)
Abstract Background The purpose of the present study is to showcase the image of Sexual Violence (SV) temporal trends through exploring differences in its prevalence rates during 1990-2017 across 195 countries and territories. Methods The SV prevalence rates were derived from the Global Burden of Disease (GBD) database during 1990-2017, worldwide. First, the Latent Growth Model (LGM) was employed for assessing the change in SV prevalence rate over time in Asia, Africa, Europe, North America, South America, Australia & Oceania, for men and women separately. Then, the change in SV prevalence rate over time was determined within countries with high and low Human Development Index (HDI). Finally, the Latent Growth Mixture Models (LGMM) were applied for identifying classes where countries within each class have similar trend of SV prevalence rate over time. Results The SV prevalence was higher among women than men and decreased in both genders over time across the world. The declining trend in SV prevalence against men is visible in both countries with high and low HDI, but SV prevalence against women in countries with low HDI shows an increase. The findings of LGMM identified six classes of SV prevalence trajectories. LGMM allocated Bermuda into the class with the highest decrease in SV prevalence against men, and Equatorial Guinea and Luxembourg into the class with the highest increase. Other countries had very slow declining trends. In terms of SV prevalence against women, LGMM allocated China, North Korea, and Taiwan into the class with the most increase among the countries in the world. Bermuda, Guyana, Mexico, Nigeria, and Saint Lucia were placed into the class which witnessed the largest decline and Angola, Congo, and Equatorial Guinea were ranked next. The trend in other countries was mostly decreasing. Conclusion Given the high economic and social burden that SV has on victims and societies, the rate of SV in most countries does not seem to have dropped remarkably and requires special attention by relevant policymakers. The SV prevalence rate is highly heterogeneous among world countries which may be due to the definitions and tools used, and more importantly, the culture norms.